The "double a" phenotype: Portending allgrove′s syndrome and averting adrenal crisis - Soumik Goswami (Indian Journal of Endocrinology and Metabolism, 2012)
Introduction: Allgrove′s syndrome is a rare autosomal-recessive disorder with only about 70 cases reported thus far and is characterized by alacrima, achalasia, and ACTH insensitivity among other clinical features. However, it has a widely variable clinical presentation, which may result in such cases remaining undiagnosed. Objective: To report a patient with impending Allgrove′s syndrome and to highlight the importance of clinical suspicion in diagnosing the same. Materials and Methods: A 2.5-year-old girl was diagnosed with impending Allgrove′s syndrome on the basis of clinical presentation, barium swallow study, Schirmer′s test, and hormonal evaluation. Results: A 2.5-year-old girl, born of non-consanguineous marriage, presented with failure to thrive and developmental delay with occasional vomiting on taking solid or semi-solid food for past 6 months. Examination revealed stunted weight (SDS of -4.4) and height (SDS of -4.76), and barium swallow showed presence of achalasia. On direct questioning, her mother mentioned presence of decreased tears on crying since birth, and Schirmer′s test confirmed the presence of dry eyes. Baseline ACTH was slightly elevated with normal basal and post-ACTH stimulation serum cortisol. Based on these findings, impending Allgrove′s syndrome was diagnosed with a plan for follow-up study of adrenal function. Conclusions: Allgrove′s syndrome may be an under diagnosed disorder as aclarima is often overlooked. However, a high index of clinical suspicion may help in avoiding adrenal crisis by diagnosing the condition early.